Elastic surface crack interaction and its engineering critical assessment within the framework of fitness-for-service standards (Fracture and Structural Integrity, 2022)
In real industrial conditions, it’s common to witness the interaction of multiple cracks such that their stress fields and crack driving forces are disturbed. For coplanar cracks, a greater hazard is expected because of the amplification phenomenon. FFS standards deal with this by proposing interaction rules and idealizing a single bonding flaw for the FAD methodology to be used. The goal of this paper is to analyze the effectiveness of this standards methodology considering twin surface semielliptical cracks on a plate under mode I loading on the interaction range using FE analyses. Results confirm that the amplification phenomena due to the interaction are higher on the interacting crack tip and progressively higher as the coplanar horizontal distance decreases. The loss of constraint was observed to decrease as the coplanar horizontal distance decreased, but little change was observed regarding its parametric angular position. A higher amplification was found at the coplanar horizontal distance on which crack interaction is to be considered meaningful, which indicates inconsistency regarding the interaction criteria used on FFS standards. To conclude, the engineering critical assessment of the bonding flaw proved to be over-conservative as the remaining operational life was observed on the assessment of the interacting flaws.
Keywords: Crack interaction; stress intensity factor; failure assessment diagram; BS 7910; API 579/ASME FFS-1